LEAN MEAT CONTENT OF PIG’S CARCASSES IN THE EIGHT SLAUGHTERHOUSES IN THE REGION OF VOJVODINA, SERBIA - Radović, Ivan; Polovinski-Horvatović, Miroslava; Mirkov, Mile; Malešević, Savo (Food and Feed Research, 2021)
The end product of the pig production is carcass. Lean meat content is a measure of the quality of the carcass. Serbia is one of only a few countries in Europe which has not yet adopted the practice of pig’s carcasses classification and failed to regulate this issue through legislation. The purpose of this work was to measure lean meat content in carcasses probed in several slaughterhouses in the Province of Vojvodina (northern Serbia) and to classify them according to the SEUROP classification. In total it was classified 65764 pig carcasses in eight different slaughterhouses. The lean mean content was measured on the slaughter line 45 minutes post mortem with the one-point puncture model. The measurement was carried out with the optoelectronic probe for the classification of pig carcasses CLASSPRO GmbH (Germany). The percentage of meat in the carcass was calculated using the mathematical model. In all eight slaughterhouses in which the measurements were done there was no poor quality (P class) pig carcass. The majority of carcasses were in the class E-excellent (35545 carcasses or 54.05% in total) and U-very good (25864 carcasses or 39.33% in total). However, a very small number of the carcasses were in the superior class with more than 60% of lean meat content, only 2072 carcases or 3.15% in total. Any future effort which the government would put in the implementation of the system of pricing of pigs based on the carcass characteristics would have enormous effect on the pig production in general. The pig producers would have the reason to invest in better farm management, selection in effort to improve the quality of the end products-pigs. In addition, the meat industry would certainly have benefits by having a higher quality raw material for further processing.
Keywords: pig production; lean meat; classification